2022
DOI: 10.1001/jamanetworkopen.2022.36273
|View full text |Cite
|
Sign up to set email alerts
|

Trends in US Emergency Department Use After Sexual Assault, 2006-2019

Abstract: ImportanceAdult sexual assault (SA) survivors experience numerous emergent health problems, yet few seek emergency medical care. Quantifying the number and types of survivors presenting to US emergency departments (EDs) after SA can inform health care delivery strategies to reduce survivor morbidity and mortality.ObjectiveTo quantify ED use and factors that influenced seeking ED care for adult SA from 2006 through 2019.Design, Setting, and ParticipantsThis cross-sectional study used SA data from the Nationwide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 44 publications
(68 reference statements)
1
23
0
Order By: Relevance
“…In addition to strengthening the acute response to SA, greater effort is needed globally to prevent sexual violence. The increased awareness and reporting of SA noted by Vogt et al 4 is certainly one step in a multilevel response needed for addressing sexual violence. 13 Comprehensive…”
Section: Openmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition to strengthening the acute response to SA, greater effort is needed globally to prevent sexual violence. The increased awareness and reporting of SA noted by Vogt et al 4 is certainly one step in a multilevel response needed for addressing sexual violence. 13 Comprehensive…”
Section: Openmentioning
confidence: 97%
“…2 Two articles in JAMA Network Open report on the incidence of CSA and adult SA cases reported to emergency departments (EDs) in Hong Kong and the US, respectively. 3,4 Wong et al 3 report on incident rates of CSA among youth presenting to EDs in Hong Kong before and during the COVID-19 pandemic. By using medical record data from EDs across Hong Kong, they found that the number of ED visits to report CSA decreased more than 50% during the pandemic.…”
mentioning
confidence: 99%
See 3 more Smart Citations